Conocemos las costumbres de las familias de nuestros amigos - Abad Tirado, Betsabe (2019)
This sufficiency work has been designed for 4-year-old children from the initial level, of the city of Trujillo in 2019, with the theme entitled “We know the customs of our friends' families”, for which I have had take into account actions that they perform daily with their parents both inside and outside their home, as well as the dialogue to express their family customs, to develop interaction skills with their peers, in the Social Personal area_x000D_ To design this learning activity, the pedagogical processes, as well as the didactic processes of the Social Personnel area, specifically for the development of orality, have been taken into account, which will allow us to promote significant learning in our children._x000D_ The strategies used allow the active participation of children, as well as teamwork, individually, the permanent dialogue of all students_x000D_ It is sought during the development of the entire activity to maintain interest in our children, as well as the development of their critical thinking - reflective, autonomy, identify the usefulness of their learning